Characterization and genetic variability of feed-borne and clinical animal/human Aspergillus fumigatus strains using molecular markers - Pena, Gabriela Alejandra (2015)
Aspergillus fumigatus, the major etiological agent of human and animal aspergillosis, is a toxigenic fungus largely regarded as a single species by macroscopic and microscopic features. However, molecular studies have demonstrated that several morphologically identified A. fumigatus strains might be genetically distinct. This work was aimed to apply PCR-restriction length fragment polymorphisms (PCR-RFLP) and random amplification of polymorphic DNA (RAPD) molecular markers to characterize a set of feed-borne and clinical A. fumigatus sensu lato strains isolated from Argentina and Brazil and to determine and compare their genetic variability. All A. fumigatus strains had the same band profile and those typical of A. fumigatus sensu stricto positive controls by PCR-RFLP. Moreover, all Argentinian and Brazilian strains typified by RAPD showed similar band patterns to each other and to A. fumigatus sensu stricto reference strains regardless of their isolation source (animal feeds or human/animal clinical cases) and geographic origin. Genetic similarity coefficients ranged from 0.61 to 1.00, but almost all isolates showed 78% of genetic similarly suggesting that genetic variability was found at intraspecific level. Finally, benA sequencing confirmed its identification as A. fumigatus sensu stricto species. These results suggest that A. fumigatus sensu stricto is a predominant species into Aspergillus section Fumigati found in animal environments as well as in human/animal clinical cases, while other species may be rarely isolated. The strains involved in human and animal aspergillosis could come from the environment where this fungus is frequently found. Rural workers and animals would be constantly exposed.